Flouting Conversational Maxims: A Study on Student Communication in Grade 9 Maroon - Ali, Hanina M.; Namol, Herlen C.; Tulud, Donnie M. (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: To investigate students' communication habits, know the causes of maxim flouting, and offer practical suggestions for enhancing class conversations. Methodology: This study used a qualitative research design, specifically discourse analysis, to investigate the flouting of conversational maxims in classroom interactions among Grade 9 Maroon students at Esperanza National High School. The study's participants comprised 30 Grade 9 students from Esperanza National High School's Maroon section. Purposive sampling was used and the data are collected through observation and audio recordings. Main Findings: The study revealed that flouting conversational maxims is widespread in classroom settings, especially among Grade 9 Maroon students. During discussions, students flouted all conversational maxims. The Maxim of Relationship (Relevance) is the most flouted maxim. Novelty/Originality of this study: This study contributes originality by examining the systematic flouting of Gricean maxims in real classroom interactions among Grade 9 students, a context underexplored in pragmatic research. Unlike previous studies focusing on teachers or digital platforms, it highlights how humor, indirectness, and over-explanation function as both challenges and learning opportunities, offering practical strategies to enhance classroom communication.